Small RNAs: The Essential Regulators in Plant Thermotolerance - Zuo, Zhi-Fang; He, Wenbo; Li, Jing; Mo, Beixin; Liu, Lin (Frontiers in Plant Science, 2021)
Small RNAs (sRNAs) are a class of non-coding RNAs that consist of 21-24 nucleotides. They have been extensively investigated as critical regulators in a variety of biological processes in plants. sRNAs include two major classes: microRNAs (miRNAs) and small interfering RNAs (siRNAs), which differ in their biogenesis and functional pathways. Due to global warming, high-temperature stress has become one of the primary causes for crop loss worldwide. Recent studies have shown that sRNAs are involved in heat stress responses in plants and play essential roles in high-temperature acclimation. Genome-wide studies for heat-responsive sRNAs have been conducted in many plant species using high-throughput sequencing. The roles for these sRNAs in heat stress response were also unraveled subsequently in model plants and crops. Exploring how sRNAs regulate gene expression and their regulatory mechanisms will broaden our understanding of sRNAs in thermal stress responses of plant. Here, we highlight the roles of currently known miRNAs and siRNAs in heat stress responses and acclimation of plants. We also discuss the regulatory mechanisms of sRNAs and their targets that are responsive to heat stress, which will provide powerful molecular biological resources for engineering crops with improved thermotolerance.